2021
DOI: 10.1080/21655979.2021.2004977
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA UBR1 promotes the proliferation, migration, and invasion but represses apoptosis of lung cancer cells via modulating microRNA-545-5p/SSFA2 axis

Abstract: Lung cancer (LC) is a malignant tumor with the highest incidence in the world, and its specific pathogenesis is still unclear. Circular RNAs (circRNAs) are a group of non-coding RNAs that play a key role in the development and progression of various cancers. The expression pattern and function of circRNAs in LC are still not completely distinct. In this study, it was aimed to study the expression and potential mechanism of circ-UBR1 in LC cells. Then it was found that circ-UBR1 was up-regulated in LC cells, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…First, UBR1 was found to be overexpressed in various types of cancers, particularly GC, which is in agreement with the results of previous studies. Previous research has also shown increased expression of cyclic UBR1 in breast [22] and lung [23] cancers. Our study using BioSign predicted that high expression of UBR1 in GC correlates with unfavorable pathological features and poor prognosis.…”
Section: Discussionmentioning
confidence: 70%
“…First, UBR1 was found to be overexpressed in various types of cancers, particularly GC, which is in agreement with the results of previous studies. Previous research has also shown increased expression of cyclic UBR1 in breast [22] and lung [23] cancers. Our study using BioSign predicted that high expression of UBR1 in GC correlates with unfavorable pathological features and poor prognosis.…”
Section: Discussionmentioning
confidence: 70%
“… 35 Additionally, the Circ_UBR1/miR-545-5p/SSFA2 axis promoted the malignant behavior of cancer cells in LC. 36 However, the Circ_0001367/miR-545-3p/LUZP1 axis suppressed cancer progression in GBM/LGG. 4 …”
Section: Mir-545 and Its Competing Endogenous Ribonucleic Acids (Cernas)mentioning
confidence: 99%
“…miR-545-3p promotes apoptosis by targeting 10 downstream PCGs, including CCND2 in NPC 57 ; KU70 57 and HDGF 6 in LC; CBLL1, 7 PRKCA, 15 and YAP1 in NSCLC 26 ; FAM98A in EC 32 ; SLC7A11 in THCA 35 ; PFKFB3 in CRC 29 ; and PPA1 in OC. 32 miR-545-5p promotes apoptosis by targeting SSFA2 in LC 36 and MDM2 in CRC. 48 …”
Section: Mir-545 Regulates Cell Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Su et al . [ 8 ] demonstrated that circUBR1 enhances lung cancer cell migration and invasion via the miR-545-5p/SSFA2 axis. Additionally, other circRNAs regulate apoptosis-related protein expression.…”
Section: Introductionmentioning
confidence: 99%